Remittances, Foreign Direct Investment, Imports and Economic Growth: Empirical Evidence from Vietnam - Minh, Cao Hong (Asian Journal of Economic Modelling, 2020)
This article aims to examine the effect of remittances, Foreign Direct Investment (FDI) and imports on economic growth in Vietnam, using a set of time series data in the period of 2000-2018, applying the Autoregressive Distributed Lag (ARDL) bounds testing approach. Also, an Error Correction Model (ECM) derived from ARDL model is utilized to check the short-run dynamics. From the empirical result of the study, it is showed that there is a long-term relationship among remittances, FDI, imports and economic growth in Vietnam during the period time of study. Specifically, remittances and imports have significantly positive impacts while FDI has negative influence on economic growth. In the short run, the growth effects of remittances and FDI are similar to those in the long run while the effect of imports is statistically insignificant. Finally, the model passes relevant diagnostic tests for time series data and the parameters are proved to be stable over time.